2012
DOI: 10.1128/jb.06746-11
|View full text |Cite
|
Sign up to set email alerts
|

CtsR Regulation in mcsAB -Deficient Gram-Positive Bacteria

Abstract: CtsR is an important repressor that modulates the transcription of class III stress genes in Gram-positive bacteria. In Bacillus subtilis, a model Gram-positive organism, the DNA binding activity of CtsR is regulated by McsAB-mediated phosphorylation of the protein where phosphorylated CtsR is a substrate for degradation by the ClpCP complex. Surprisingly, the mcsAB genes are absent from many Gram-positive bacteria, including streptococci; therefore, how CtsR activity is modulated in those bacteria remains unk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 48 publications
(69 reference statements)
0
12
1
Order By: Relevance
“…CtsR, a major repressor for the Clp ATPases (34,35), mainly regulates the expression of stress response genes by recognizing a tandemly repeated heptanucleotidic sequence known as the CtsR box (35). We recently demonstrated that CtsR is accumulated in larger amounts in cells that do not have a functional ClpL protein (36). This finding was interesting since in most Gram-positive bacteria, CtsR is degraded by ClpCP (37).…”
mentioning
confidence: 76%
See 3 more Smart Citations
“…CtsR, a major repressor for the Clp ATPases (34,35), mainly regulates the expression of stress response genes by recognizing a tandemly repeated heptanucleotidic sequence known as the CtsR box (35). We recently demonstrated that CtsR is accumulated in larger amounts in cells that do not have a functional ClpL protein (36). This finding was interesting since in most Gram-positive bacteria, CtsR is degraded by ClpCP (37).…”
mentioning
confidence: 76%
“…Our previous study showed that the CtsR protein accumulated in large amounts in a clpL-deficient S. mutans strain (36). Further analyses suggested that the accumulated CtsR (HisCtsR) is present predominantly in the pellet fraction and not in the soluble fraction of the cell lysate from the ⌬clpL strain (IBSJ3/pIBJ1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A markerless gene replacement method that utilized the Cre-loxP-based recombination system was used for deleting clpC, clpE and clpX genes as described previously (Banerjee & Biswas, 2008;Biswas et al, 2007;Tao et al, 2012). The mutant constructs were verified by PCR and sequencing.…”
Section: Methodsmentioning
confidence: 99%